A cross‐sectional survey of moral distress and ethical climate – Situations in paediatric oncology care that involve children’s voices - Päivi Ventovaara; Margareta af Sandeberg; Gitte Petersen; Klas Blomgren; Pernilla Pergert (Nursing Open, 2022)
Abstract Aim To assess experiences of morally distressing situations and perceptions of ethical climate in paediatric oncology care, with a focus on situations that involve children's voices. Design Cross‐sectional survey. Methods Registered Nurses at all four paediatric oncology centres in Denmark were asked to complete a web‐based questionnaire with Danish translations of the Swedish Moral Distress Scale‐Revised (MDS‐R) and the Swedish Hospital Ethical Climate Survey‐Shortened (HECS‐S). Data analysis included descriptive statistics and non‐parametric correlation tests. Results Nurses (n = 65) perceived morally distressing situations as rather uncommon, except for those that involved shortage of time, poor continuity of care and unsafe staffing levels. Most nurses (83%) found it disturbing to perform procedures on school‐aged children against their will, and 20% reported that they do this often. Perceptions of ethical climate were positive and healthcare professionals were perceived to be attentive to children's wishes.